2014
DOI: 10.1080/02692171.2013.858667
|View full text |Cite
|
Sign up to set email alerts
|

The financial fragility and the crisis of the Greek government sector

Abstract: The purpose of this paper is to develop Minskyan financial fragility indices for the government sector and to examine the financial structure of the Greek government before and after the onset of the sovereign debt crisis in 2009. We provide empirical evidence that clearly shows the growing financial fragility of the Greek public sector in the 2000's. We also assess the effectiveness of the implemented bailout adjustment programmes in Greece and claim that the conducted austerity measures and fiscal consolidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
9
0
5
Order By: Relevance
“…[5] The empirical analysis of financial fragility is not restricted to the private sector. Argitis and Nikolaidi (2014) applied Minskian analysis to the Greek government sector. This study also showed that since 2003 the Greek government sector has shifted to an ultra-Ponzi regime in which the government runs a primary deficit.…”
Section: Notesmentioning
confidence: 99%
“…[5] The empirical analysis of financial fragility is not restricted to the private sector. Argitis and Nikolaidi (2014) applied Minskian analysis to the Greek government sector. This study also showed that since 2003 the Greek government sector has shifted to an ultra-Ponzi regime in which the government runs a primary deficit.…”
Section: Notesmentioning
confidence: 99%
“…No obstante, cuando esta combinación privilegia el financiamiento externo, y ello se conjuga con un ambiente de inestabilidad financiera, puede poner en riesgo la supervivencia de las empresas, y transmitir sus efectos negativos al resto de la economía. Debido a que la inestabilidad financiera se ha presentado con mayor frecuencia, el estudio de la estructura financiera de las empresas debe constituir un tema de la agenda de la ciencia económica, que no solo adquiera relevancia en momentos de crisis, como sucedió recientemente con la crisis subprime en 2008 (Beshenov, S., y Rozmainsky I., 2015;Argitis, G. y Nikolaidi M., 2014;Mulligan, R., Lirely, R. y Coffee D., 2014). Más aún, considerando que, como lo expuso Minsky (1986) en su Hipótesis de Inestabilidad Financiera, estas son resultado de procesos que encuentran su explicación en los procesos de inversión y financiamiento de las empresas.…”
Section: Introductionunclassified
“… 1. Argitis and Nikolaidi (2014) presented evidence showing the growing financial fragility of the Greek public sector in the 2000s. …”
mentioning
confidence: 99%